Estimation of the organ of origin of peri-ampullary malignancy by preoperative CT scan. (March 2023) - Amr, Bassem; MacCormick, Andrew; Miles, Gemma; Shahtahmassebi, Golnaz; Roobottom, Carl; Stell, David
Background: Tumors occurring within the pancreatic head commonly arise from the pancreas, duodenal ampulla, distal bile duct, or duodenum. However, they are difficult to distinguish on standard preoperative imaging. Purpose: To assess the ability of specialist reporting of preoperative computed tomography (CT) scans to determine the organ of origin of pancreatic cancer (PC). Material and Methods: Blinded re-reporting of preoperative imaging from five hospitals was undertaken of a consecutive cohort of 411 patients undergoing surgery for PC between January 2006 and May 2014. Radiological identification of tumor site was determined by the presence of the main tumor bulk within the pancreatic head parenchyma and estimation of the pathological organ of origin of the PC was based on all the reported features. Results: Each pathological tumor type was noted to have distinct radiological features. Localization of a visible tumor within the pancreatic parenchyma was seen most commonly in PC (92%) than other tumor types ( P  < 0.0001). Local invasion into the duodenum was a characteristic feature seen in 79% of patients with ampullary tumors and isolated dilation of the bile duct without dilation of the pancreatic duct was seen most commonly in patients with ampullary or bile duct cancer. In the assessment of tumor origin, good agreement (kappa = 0.6, 0.51–0.68) was noted between the consensus radiology opinion and the final histology result. Overall accuracy was greatest for ampullary cancer (88.1%) and lowest for PC (83.2%). Conclusion: Radiological assessment of preoperative imaging provides a high degree of accuracy in predicting the organ of origin of peri-ampullary cancer.